2011
DOI: 10.1089/tmj.2010.0175
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Health Professionals Through Information and Communication Technologies: A Systematic Review of the Effects of Information and Communication Technologies on Recruitment and Retention

Abstract: Despite the conclusions of 9 of 13 studies reporting a possible positive influence of ICTs on the recruitment and retention of healthcare professionals, these results highlight the need of a deeper reflection on that topic. Therefore, more research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The third review defined the three main supportive relationships identified in the nursing literature [26]. The fourth one explored the impact of interventions using information and communication technologies (ICTs) on recruitment and retention of healthcare professionals in less-served regions [27], while the fifth review described stages related to recruitment and retention of health professionals to rural health careers [28]. As shown in Table 1, three of the reviews [24,25,27] met more than 66% of the PRISMA appraisal criteria while the other two [26,28] met more than 50% of them.…”
Section: Resultsmentioning
confidence: 99%
“…The third review defined the three main supportive relationships identified in the nursing literature [26]. The fourth one explored the impact of interventions using information and communication technologies (ICTs) on recruitment and retention of healthcare professionals in less-served regions [27], while the fifth review described stages related to recruitment and retention of health professionals to rural health careers [28]. As shown in Table 1, three of the reviews [24,25,27] met more than 66% of the PRISMA appraisal criteria while the other two [26,28] met more than 50% of them.…”
Section: Resultsmentioning
confidence: 99%
“…To what extent can ICTs create favorable conditions that attract nurses and reinforce stability in the workforce? A systematic review was undertaken on the effect of ICTs on retention and recruitment of health care professionals [62]. The results revealed that, in 9 out of the 13 studies, ICT use demonstrated a positive, though often indirect, influence on recruitment and retention.…”
Section: Discussionmentioning
confidence: 99%
“…It is inspired by local 12-14 and international 16 studies, as well as a systematic review on the impact of ICT on the recruitment and retention of the healthcare workforce. 15 Based on the premise that job satisfaction is an important dimension in nurse retention, [33][34][35] we propose in this conceptual map ( Fig. 2) a set of factors affecting nurse job satisfaction, including professional autonomy, 36 professional development, 37,38 feeling of professional isolation, 35 level of stress, 33 and quality of care.…”
Section: Methodsmentioning
confidence: 99%
“…7,11 Some studies have analyzed the influence of telehealth on workforce recruitment and retention factors, [12][13][14][15][16] but few studies have addressed the influence of telehealth on nursing practice, particularly with respect to nurse recruitment and retention factors. [17][18][19][20][21] Thus, we initiated a project, in collaboration with decision makers, entitled ''Supporting Work Practices Through Telehealth: Impact on Nurses in Outlying Regions.''…”
Section: Introductionmentioning
confidence: 99%